Choosing placental hypoxic-ischemic measures that have clinical implications in child development and diseases. (12th December 2022) - Zhao, Yanjun; Zhang, Huijuan; Chen, Yan; Wu, Ting; Zhang, Jun
Abstract: Purpose: Placental hypoxic-ischemic pathology is one of the common causes for adverse outcomes. But there is no commonly accepted evaluation system on specific morphological and histopathological measures of the placenta. Objective: This study aims to systematically select several core placental hypoxic-ischemic measures that have a high prognostic relevance to child health. Methods: We used data from the Collaborative Perinatal Project, a multicenter prospective cohort study that recruited over 55, 000 pregnant women and followed their offspring to 7 years old. Women who had information on placental pathology and child outcomes were included. 57 placental measures considered to be relevant to hypoxia-ischemia were selected. Apgar score, intelligence quotient, preeclampsia, birth weight and subclinical neurology injuries were chosen as outcomes. The least absolute shrinkage and selection operator (LASSO) procedure as well as training and testing methods were used to select a more efficient and simpler placental hypoxic-ischemic measures that may have clinical implications. Results: Of the 57 measures, 7 were selected as candidates by LASSO. Based on the training and testing methods, we retained placental measures with a higher odds ratio of child morbidity. We further narrowed down to four measures that had the highest prognostic relevance. They were: short cord length (ΣOR = 8.51), calcification of cut surface (ΣOR = 8.31), opaque membranes (ΣOR = 5.26), Hofbauer cells in terminal villi (ΣOR = 4.69). Conclusions: Our four-measure system is relatively simple and closely related to the child health. It may be used as a novel placental hypoxic-ischemic evaluation criterion, and function as the first line tool for future research.